Integrated Vascular–Cognitive Assessment: Toward a Predictive Model for Stroke and Cognitive Decline in Atherothrombotic Carotid Disease - Yuldashev, Sardorbek (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2025)
Recent evidence demonstrates that the risk of ischemic stroke and cognitive decline in patients with atherothrombotic carotid disease cannot be explained by stenosis severity alone. Modern studies emphasize the multifactorial nature of cerebrovascular risk, encompassing hemodynamic insufficiency, plaque instability, systemic inflammation, and impaired neurocognitive reserve. This review synthesizes current literature on the anatomical, functional, biochemical, and cognitive determinants of cerebrovascular outcomes. Research by Abboud et al. (2020) and Bonati et al. (2018) highlights the prognostic value of plaque morphology and individualized management of carotid stenosis. Functional studies by Markus and Cullinane (2001) and Xu et al. (2022) demonstrate that reduced cerebrovascular reserve predicts both ischemic events and cognitive decline. Inflammatory mechanisms identified by Spence (2020) and Rosenberg (2017) further explain disease progression and neuronal injury. The integration of these findings supports the creation of comprehensive predictive models combining carotid imaging, cerebrovascular reactivity, systemic biomarkers, and cognitive assessment. Such models provide superior prognostic accuracy, enable earlier risk stratification, and promote personalized prevention strategies aimed at reducing stroke incidence and preserving cognitive health.